Innovative Electrochemical Processing for Copper Removal from Carbon Saturated Iron Melt Using Na2S-FeS Molten Sulfide. Issue 3 (4th March 2021) - Lu, Zhihao; Liu, Chengjun; Wang, Yeguang
Abstract : Innovative electrochemical processing was proposed in this paper to remove residual copper from carbon saturated iron melt. A direct current electric field was applied to treat the copper-bearing molten iron with molten sulfide flux between a cathode immersed in the sulfide flux and an anode immersed in the molten iron, and a better decopperization effect was achieved with the action of the electric field. Including the copper removal ratio increased to 94%, the distribution ratio of copper between the sulfide and iron increased by about four times, and the sulfur content in the iron melt was decreased by about 50%. Electrochemical tests were carried out to study the reasons for those effects. The results indicated that the electrodeposition of Cu + on the cathode promotes the mass transfer of Cu from iron melt to molten sulfide, and the excess S 2− in the iron melt was oxidized to volatile sulfur on the anode. The molten sulfide has been widely concerned in pyrometallurgy for its potential to remove copper from iron-based melts, and this study verified that molten sulfide could also be used as an electrolyte for electrorefining of iron-based melts.